To solve the quadratic equation \( 46x^2 - 138x = 0 \) by factoring out the greatest common factor (GCF), we start by identifying the GCF of the terms involved.
The GCF of \( 46x^2 \) and \( -138x \) is \( 46x \).
Now, we factor \( 46x \) out of the equation:
\[ 46x(x - 3) = 0 \]
Now, we can set each factor equal to zero to find the solutions:
-
\( 46x = 0 \)
- This gives \( x = 0 \).
-
\( x - 3 = 0 \)
- This gives \( x = 3 \).
Thus, the solutions are \( x = 0 \) and \( x = 3 \).
The correct response is: The solutions are \( x = 0 \) and \( x = 3 \).